Pesantren's Strategy in Implementing Vocational Education Policy Through Vocational Training Centers (VTC) - Lingga Fahrurrosi; Khoridatul Bahiyah; Nurmila Binti Marzuki (Universitas Islam Negeri Sumatera Utara, 2025)
This study examines the implementation of vocational education policy at Miftahul Ulum Islamic Boarding School in Gondanglegi, Malang. The research is significant due to unemployment issues and the mismatch between education and the job market, which highlight a weak vocational policy implementation within the unique and under-researched context of pesantren. Using a qualitative case study approach, data were collected through in-depth interviews, participant observation, and document analysis, and then validated with source triangulation. The data analysis followed an interactive model, including data reduction, display, and conclusion drawing. Findings show that the school's Community Vocational Training Center (VTC) focuses on Visual Communication Design (VCD). This specialization is strategic, as it is highly relevant and supported by competent internal staff. The curriculum emphasizes mastering Corel Draw software, with graduation standards based on project completion. Graduates further develop skills through external internships. However, this VTC faces challenges like inadequate operational funding, a lack of supervision, and structural management issues. To address these, the management plans to reorganize its administration and forge new partnerships to more effectively place graduates in the workforce.